Burnt Offering. - Metelerkamp, Joan (Modjaji Books, 2008)
Burnt Offering is Joan Metelerkamp's seventh collection of poems. The title comes from a poem in a cycle that embodies the labours of the medieval alchemists - heating and burning, transformation of passionate intensity, the search for an enduring element. In the process malignant doubt is burnt off, and what takes its place is trust in the everyday: ""take this day, here, take it all its clarity, all its gold""--Like all of Metelerkamp's work, these generous poems draw on and weave together, with her distinctive energy and passion, the details of family and rural life, dreams, landscapes an